2022
DOI: 10.3390/md20050278
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Doxorubicin-Loaded Carboxymethyl-β-Cyclodextrin/Chitosan Nanoparticles with Antioxidant, Antitumor Activities and pH-Sensitive Release

Abstract: In this study, chitosan nanoparticles (HF-CD NPs) were synthesized by an ionic gelation method using negatively charged carboxymethyl-β-cyclodextrin and positively charged 2-hydroxypropyltrimethyl ammonium chloride chitosan bearing folic acid. The surface morphology of HF-CD NPs was spherical or oval, and they possessed relatively small particle size (192 ± 8 nm) and positive zeta potential (+20 ± 2 mV). Meanwhile, doxorubicin (Dox) was selected as model drug to investigate the prepared nanoparticles’ potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In addition to sensitivity to pH, chitosan is low toxicity, biocompatible, has antibacterial properties, mucoadhesive properties, and permeation-enhancing effects [ 94 , 95 ]. Due to these beneficial characteristics of chitosan, many researchers have used chitosan in various pH-sensitive release systems for liver cancer [ 96 , 97 , 98 , 99 , 100 ]. Mi et al [ 96 ] reported pH-sensitive drug delivery for DOX based on Carboxymethyl-β-Cyclodextrin/Chitosan Nanoparticles.…”
Section: Internal Stimuli-responsive Drug Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sensitivity to pH, chitosan is low toxicity, biocompatible, has antibacterial properties, mucoadhesive properties, and permeation-enhancing effects [ 94 , 95 ]. Due to these beneficial characteristics of chitosan, many researchers have used chitosan in various pH-sensitive release systems for liver cancer [ 96 , 97 , 98 , 99 , 100 ]. Mi et al [ 96 ] reported pH-sensitive drug delivery for DOX based on Carboxymethyl-β-Cyclodextrin/Chitosan Nanoparticles.…”
Section: Internal Stimuli-responsive Drug Delivery Systemmentioning
confidence: 99%
“…Due to these beneficial characteristics of chitosan, many researchers have used chitosan in various pH-sensitive release systems for liver cancer [ 96 , 97 , 98 , 99 , 100 ]. Mi et al [ 96 ] reported pH-sensitive drug delivery for DOX based on Carboxymethyl-β-Cyclodextrin/Chitosan Nanoparticles. In vitro release showed higher cumulative release rates of DOX from HF-DOX-CD NPs at a low pH, than cumulative release at neutral pH or slightly basic pH due to the tendency of chitosan nanoparticles to swell at low pH, and also, due to the acidic pH, the protons might penetrate the interior and attack the inner secondary bonds of the nanoparticle.…”
Section: Internal Stimuli-responsive Drug Delivery Systemmentioning
confidence: 99%
“…28 At the same time, a large number of studies have shown that the incorporation of CMβCD into nanoparticles for drug delivery of various bioactive compounds can enhance solubility and stability, control drug release, improve bioavailability, increase drug loading capacity, and reduce toxicity. 29 However, single carboxymethyl-β-cyclodextrin lacks tumor targeting and penetration in vivo, so surface modification is necessary to improve their performance as delivery drugs. If a cyclodextrin derivative can be designed to effectively deliver siRNA and chemotherapeutics simultaneously, it will expand its application as a delivery material.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins (CDs) are biocompatible cyclic oligosaccharides with a hydrophilic periphery and a well-defined hydrophobic cavity capable of binding various organic molecules, including biologically relevant compounds. Compared to calixarenes, which are poorly water-soluble, conformationally unstable, and also have a cavity structure, supramolecular nanocapsules based on cyclodextrins (CDs) have an important potential in cancer therapy due to their good biocompatibility, low toxicity to healthy cells, and reliable delivery and release of therapeutic agents to specific targets. , Furthermore, natural compounds have been explored as delivery systems for plasmid DNA and siRNA, making them attractive candidates for siRNA delivery. , Carboxymethyl-β-cyclodextrin (CMβCD), as a derivative of cyclodextrin, also has the properties of cyclodextrin . At the same time, a large number of studies have shown that the incorporation of CMβCD into nanoparticles for drug delivery of various bioactive compounds can enhance solubility and stability, control drug release, improve bioavailability, increase drug loading capacity, and reduce toxicity . However, single carboxymethyl-β-cyclodextrin lacks tumor targeting and penetration in vivo , so surface modification is necessary to improve their performance as delivery drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The process is entirely performed in aqueous medium; thus, it is not suitable for the effective encapsulation of lipophilic molecules. Recently, authors demonstrated that anionic cyclodextrins (CDs), such as carboxymethyl-β-CD (CM-β-CD) and sulfobutylether-β-CD (SBE-β-CD), can electrostatically interact with CS to develop NPs for drug delivery [ 43 , 44 , 45 , 46 ]. Moreover, due to their hosting capacities, these CDs can include hydrophobic drugs [ 47 , 48 , 49 , 50 ], improving their physical–chemical properties (first of all, aqueous solubility).…”
Section: Introductionmentioning
confidence: 99%